2009
DOI: 10.1111/j.1537-2995.2009.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the supply and demand for clinical laboratory professionals in the United States

Abstract: Medical technologists (MTs) and technicians fill key roles in blood centers and hospital transfusion services. There is a concern that the number of new technologists and technicians entering the field is insufficient to keep up with demand created by the retirement of current personnel and continuing technological innovation. The American Society for Clinical Pathology reported in March 2009 that laboratories across the United States were struggling to fill MT and medical laboratory technician (MLT) positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…This need for laboratory automation comes from an increased demand for clinical microbiology laboratory services, despite growing staffing challenges [9][10][11]. Successful automation of a laboratory requires a thorough assessment and appropriate refinement of all laboratory workflow practices that might impact system efficiency [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This need for laboratory automation comes from an increased demand for clinical microbiology laboratory services, despite growing staffing challenges [9][10][11]. Successful automation of a laboratory requires a thorough assessment and appropriate refinement of all laboratory workflow practices that might impact system efficiency [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This need for laboratory automation comes from an increased demand for clinical microbiology laboratory services, despite growing staffing challenges. (8-10) Successful automation of a laboratory requires a thorough assessment and appropriate refinement of all laboratory workflow practices that might impact system efficiency. (11, 12) This includes consideration of extending service delivery to a twenty-four hour day, seven days per week (24/7) schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that TLA can also improve laboratory workflow, efficiency, and reproducibility(5, 8, 14, 15) while reducing errors. (3, 7) Staffing reductions of approximately 30% have been reported after automation despite a 27% increase in average laboratory-workload per day.…”
Section: Introductionmentioning
confidence: 99%
“…If successful, the certification initials MLS(ASCP) can be added as a suffix, i.e., Jane Smith, MLS(ASCP). The title Medical Technologist or Clinical Laboratory Scientist has recently been replaced with Medical Laboratory Scientist to better define laboratory professionals 1 . There is also a written examination offered by the ASCP for individuals employed in blood banking who have baccalaureate degrees but who are not certified medical laboratory scientists.…”
Section: Introductionmentioning
confidence: 99%